Brand Experience, Brand Satisfaction, E-Wom, Brand Trust And Brand Loyalty - Ni Wayan Diah Widnyasari; Gede Sri Darma (UNIVED Press, 2025)
Success company No regardless of role customer. Customers can quickly leave A brand if they do not have a strong sense of attachment, even though loyal customers generate the highest income. Strong brands can create loyalty brand terms for consumers to see the brand as a product or a good service. Study This aims To analyze the influence of experience brand, satisfaction brand and E-WOM against loyalty brand with trust brand as variable mediation. Amount sample as many as 190 people. Data analysis techniques used are descriptive statistics and statistical inferential, SEM PLS. Based on the results, analysis found that experience brand, satisfaction brand, and E-WOM influence positively and significantly loyalty brand. Trust brands can meditate in a way that partially influences trust, satisfaction, and E-WOM against loyalty brands. Research results Mean that the more tall trust brand, satisfaction brand and consumer E-WOM on Kompas.com, the higher it is loyalty brand consumers towards Kompas.com.